2022
DOI: 10.2147/cia.s364222
|View full text |Cite
|
Sign up to set email alerts
|

The Median Effective Dose and Bispectral Index of Remimazolam Tosilate for Anesthesia Induction in Elderly Patients: An Up-and-Down Sequential Allocation Trial

Abstract: Purpose Remimazolam is a new type of ultrashort benzodiazepine drug with an unclear optimal dose for general anesthesia induction in elderly patients aged >60 years. Therefore, this study aimed to determine the effective dose of remimazolam tosilate induction and explore its correlation with the bispectral index (BIS). Patients and Methods A total of 42 elderly patients were divided into two age groups: 60–69 (group A) and 70–85 (group B) years. An initial dose of 0.1mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…19,21,22 RT, a new ultra-short-acting type of GABA A receptor agonist, has been widely used in procedural sedation and general anesthesia due to its promising properties, including a rapid onset, short recovery time and stable hemodynamics. 23,24 Our results showed that the hemodynamic fluctuation (∆MAP) in group LR and group E were significantly lower than that in group HR, while the ∆HR between the three groups were noted no significant difference. Although the average difference of ∆MAP between the three groups are only a few mmHg (19.67 vs 18.45 vs 24.85 mmHg, respectively), these minor hemodynamic changes may affect the balance between myocardial oxygen supply and demand, especially for patients with potential myocardial ischemia risk.…”
Section: Discussionmentioning
confidence: 58%
“…19,21,22 RT, a new ultra-short-acting type of GABA A receptor agonist, has been widely used in procedural sedation and general anesthesia due to its promising properties, including a rapid onset, short recovery time and stable hemodynamics. 23,24 Our results showed that the hemodynamic fluctuation (∆MAP) in group LR and group E were significantly lower than that in group HR, while the ∆HR between the three groups were noted no significant difference. Although the average difference of ∆MAP between the three groups are only a few mmHg (19.67 vs 18.45 vs 24.85 mmHg, respectively), these minor hemodynamic changes may affect the balance between myocardial oxygen supply and demand, especially for patients with potential myocardial ischemia risk.…”
Section: Discussionmentioning
confidence: 58%
“…Remimazolam has been approved for use as an anesthetic and sedative for adults; however, the scope of approval varies from country to country, e.g., it is used as a general anesthetic in Japan and South Korea and a procedural sedative also in South Korea, the USA, China, and European countries [1]. After market approval, remimazolam has been used as sedative in various procedures, such as gastrointestinal endoscopy, colonoscopy, and bronchoscopy [4,5], and as anesthetic in various surgeries, such as urologic surgery, robotic gastrectomy, and cardiac surgery [6][7][8][9][10][11][12][13][14].…”
Section: Wwwembseorgmentioning
confidence: 99%
“…In a situation where a syringe pump may not be used, bolus dosing of remimazolam may be adopted; however, it is not currently recommended because stable injection may not be ensured [17]. Recently, several studies on bolus dosing of remimazolam for inducing anesthesia and sedation have been conducted (Table 1) [4,10,21,22]. Dai et al [4] suggested that complete anesthesia induction without rescue sedation can be achieved with 0.4 mg/kg of remimazolam; however, 0.3 mg/kg of remimazolam is more appropriate considering the dose-dependent risk of remimazolam-induced hypotension.…”
Section: Clinical Doses Of Remimazolammentioning
confidence: 99%
See 1 more Smart Citation
“…Second, commercially available infusion pumps and pharmacokinetic models for the target-controlled infusion of remimazolam are limited. Third, anesthesia depth monitoring indices, such as the bispectral index (Medtronic, Ireland) or patient state index (Masimo, USA), are not well correlated with loss of consciousness in general anesthesia with remimazolam [ 10 , 11 ]. Fourth, interactions with other drugs used for general anesthesia, particularly opioid analgesics, have not been studied sufficiently.…”
mentioning
confidence: 99%